A Multilevel Framework of Racism as a Barrier to Teachers' Implementation of Culturally Relevant Pedagogy - Olga Pagán (SAGE Publishing, 2022)
Culturally relevant pedagogy (CRP; e.g., Ladson-Billings, 1995) is a set of beliefs and practices that aim to serve culturally and linguistically diverse student learners. Although a large body of work describes its tenets and permutations, and its implications for students, less work has been done to outline the myriad barriers that teachers face when trying to implement CRP. This paper addresses this gap by proposing a race-conscious, multilevel, ecological framework to illuminate the societal, institutional, and individual obstacles that teachers must navigate in the pursuit of CRP. Implications for teacher training and development are discussed.